2018
DOI: 10.3389/fimmu.2018.01713
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Regulates Apoptosis and Inflammation in a Murine Model of Experimental Autoimmune Uveitis

Abstract: Uveitis is characterized as a common cause of blindness worldwide. Aryl hydrocarbon receptor (AhR), a ligand-activated nuclear receptor, has been implicated to play a role in human uveitis, although the exact mechanisms remain poorly understood. The purpose of this study was to enhance our knowledge concerning the role of AhR during intraocular inflammation. We immunized wild-type and AhR-knockout C57BL/6J mice with IRBP651–670 to induce experimental autoimmune uveitis (EAU). Disease severity was evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 68 publications
(82 reference statements)
2
40
0
Order By: Relevance
“…Thus, I3C prevented ischemic reperfusion-induced inflammation and improved neurobehavioral symptoms in a cerebral ischemic stroke model [ 41 , 42 ]. AhR agonists also reversed pro-inflammatory gene expression in experimental autoimmune uveitis [ 11 ]. Here, we found that I3C prevented light-induced CCL2 expression in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, I3C prevented ischemic reperfusion-induced inflammation and improved neurobehavioral symptoms in a cerebral ischemic stroke model [ 41 , 42 ]. AhR agonists also reversed pro-inflammatory gene expression in experimental autoimmune uveitis [ 11 ]. Here, we found that I3C prevented light-induced CCL2 expression in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…In the ocular compartment, AhR knockout triggers apoptosis and inflammation in experimental autoimmune uveitis [ 11 ]. AhR deficiency also disturbs extracellular matrix biology, leading to an AMD-like pathology in mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with AHR agonists, 6-formylindolo(3,2-b)carbazole (FICZ) and 2-(1'H-indole-3'carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE), can inhibit interferon-gamma (IFN-γ), interleukn-17 (IL-17), and induced IL-22 production by PBMCs, leading to a decrease in overall inflammation. Similarly, AHR activation has shown therapeutic effects in an experimental model of uveitis, which is an intraocular inflammatory disease [128,129]. It has also been shown that the AHR is involved in regulating apoptosis and inflammation in experimental autoimmune uveitis (EAU).…”
Section: The Ahr and Ocular Diseasesmentioning
confidence: 99%
“…It has also been shown that the AHR is involved in regulating apoptosis and inflammation in experimental autoimmune uveitis (EAU). Ahr −/− mice subjected to EAU show evidence of significantly increased macrophage presence and stronger polarization from the M2 (involved in tissue repair) to the M1 (proinflammatory) phenotype compared to Ahr +/+ mice [129]. Ahr −/− EAU mice also display higher protein expression levels of the M1 marker subset, inducible nitric oxide synthase (iNOS) and CD16, and lower protein expression levels of the M2 marker subset, arginase-1 (Arg-1) and CD206, relative to Ahr +/+ EAU mice [129].…”
Section: The Ahr and Ocular Diseasesmentioning
confidence: 99%
“…In AhR À/À mice, the incidence of liver cancer induced by diethylnitrosamine (non-AhR ligand) was higher than that in wild-type (AhR þ/þ ) mice, because high levels of oxidative stress and stable expression of TGF-B promoted tumor development in AhR À/À male mice (Fan et al 2010). Huang, YK et al discovered that after experimental autoimmune uveitis induction, AhR À/À mice had more severe clinical and histopathological findings of uveitis than AhR þ/þ mice (Huang et al 2018). More recently, Iu et al found that AhR can inhibit inflammation, oxidative stress and apoptosis caused by cigarette smoke through mechanisms involved in RelB gene (NF-B member) regulation (Iu et al 2017).…”
Section: The Role Of Ahr In Tumormentioning
confidence: 99%